LEGAL, FINANCIAL AND MARKETING ASPECTS OF GAMES OF CHANCE IN THE REPUBLIC OF SERBIA (Heritage, 2021)
Gambling and betting activities have always attracted the attention of both the organizers and users of games of chance and the legislators. At the very beginning of the paper, the author analyzes the harmful effects of gambling and betting, as well as the development and spread of social deviations due to the uncontrolled consumption of games of chance. The paper aims to indicate in what way, and to what extent, the legislation in the Republic of Serbia regulates gambling and betting activities, i.e., the impact of legislation on the financial and marketing business aspects of the three most represented organizers of games of chance in this area. The first part of the paper points to the numerous specifics characterizing gambling and betting activities, i.e. special legal regulations that regulate each business segment in this activity. The second part of the paper presents a financial overview of the performance indicators of the three most represented organizers of games of chance. The final part of the paper is dedicated to the legal possibilities and restrictions to advertising games of chance, or the efforts of all three organizers to boost the promotion of their business by taking on socially responsible activities, keeping it with such an approach within the legal framework.
Keywords: gambling and betting activities, games of chance, Law on games of chance, obligations of organizers, socially responsible business